Extrarenal Pelvis in a Cat - Diagnosis by Scintigraphy - Brose, Mariana de Mattos; Schaefer, Gabriela da Cruz; Becerra, José Ricardo Herrera; Mello, Fabíola Peixoto da Silva; Dalto, André Gustavo Cabrera; Berdichevski, Eduardo Herz; Costa, Fernanda Vieira Amorim da; Ferreira, Márcio Poletto (Acta Scientiae Veterinariae, 2022)
Background: In people, extrarenal pelvis is a normal anatomical variant, characterized by the protusion of the pelvis out of the renal hilum, which can be associated with other anomalies, or predispose to stasis or infection. While other diagnostic imaging methods provide anatomical and morphological information about the kidney, scintigraphy allows to determine the renal function and has greater sensitivity in the detection of functional alterations. The aim of this work is to report the case of an asymptomatic cat diagnosed with extrarenal pelvis detected by scintigraphy, which presented alterations in laboratory and renal imaging tests, and absence of associated obstructive process. Case: A 7-year-old mixed-breed female cat was evaluated for a routine health assessment at the Veterinary Teaching Hospital of the Federal University of Rio Grande do Sul (HCV-UFRGS). When performing the imaging and laboratory tests, renal alterations compatible with chronic kidney disease were found in the abdominal ultrasonography examination and in serum creatinine levels. Therefore, it was decided to perform scintigraphy evaluation to better assess renal function. Dynamic renal scintigraphy with 99mTcDTPA revealed an evident concentration of the radiotracer in the left kidney with effective elimination only after the diuretic stimulus. The right kidney exhibited less concentration of the radiotracer but showed effective elimination before the diuretic stimulus. Image analysis suggested the presence of an extrarenal pelvis on the left side. The relative renal uptake was 68% for the left kidney and 32% for the right kidney. The glomerular filtration rate was 1.65 mL/min/kg. Static renal scintigraphy with 99mTcDMSA revealed irregularity in the distribution of the radiotracer in both kidneys, showing less activity in the caudal pole of the left kidney. The right kidney was apparently reduced and with less activity, especially in the medial portion. The relative renal uptake was 65% for the left kidney and 35% for right kidney, while the absolute renal uptake of the left kidney was 33% and that of the right kidney was 17%. The alteration described in the left kidney, in correlation with dynamic renal scintigraphy, suggested an aspect of lower activity in the caudal pole due to the presence of activity in the extrarenal pelvis. The left kidney was classified as presenting normal renal function and there was moderate to severe deficit of renal function on the right side. Discussion: Chronic kidney disease may be present before clinical signs and biochemical abnormalities are identified. In this report, the animal was referred for a routine evaluation and showed no clinical signs nor alterations on physical examination. However, as renal morphological alterations were seen on ultrasonography and the cat presented mild azotemia, it was decided to perform two renal scintigraphy exams. Despite the radiotracer elimination from the left kidney was seen only after the diuretic stimulus, dynamic renal scintigraphy did not show any obstructive process. This delay on elimination was probably a result of the anatomical variant called extrarenal pelvis. In the static renal scintigraphy, it was possible to evaluate morphological changes in the kidneys and suggest less activity in the caudal pole of the left kidney, due to the presence of activity in the extrarenal pelvis, apparently causing the mentioned defect. The correct diagnosis of morphological changes is essential and for this purpose the best combination of imaging tests is necessary. Renal scintigraphy was fundamental, in this case, for the diagnosis of extrarenal pelvis in one of the kidneys, an abnormality not reported in the feline species within the literature researched by the authors. In addition, renal scintigraphy helped to guide the clinical management of the patient described in this report. Keywords: renal scintigraphy, chronic kidney disease, ultrasonography, nuclear medicine. Título: Pelve extrarrenal em uma gata - diagnóstico por cintilografia. Descritores: cintilografia renal, doença renal crônica, ultrassonografia, medicina nuclear.